UJI DAYATARIK TIGA MERK ATRAKTAN UNTUK PENGENDALIAN HAMA LALAT BUAH (Bactrocera spp.) PADA TANAMAN SAYURAN DAN BUAH-BUAHAN - Juniawan Juniawan (AgriPeat, 2021)
Fruit flies are an insect whose existence is very detrimental because of their role and function as the main pests for vegetable and fruit farmers. For that, we need technology that can suppress the population to increase crop production. The purpose of this study is to obtain information about the ability of three attractant brands on the market to attract male fruit flies, namely Ferokop, Petrogenol, and Milabu. This research used a quantitative exploratory method with collecting data on the number of male fruit fly imago trapped and harvested. The treatment for each type of attractant was repeated four times so that there were 12 bottles of traps in total. The harvest of fruit flies is carried out every day and counted manually using a hand counter. This data obtained were then tabulated and analyzed with ANOVA at the level significant of 5%. If there is a significant difference, then a further test is carried out with the Least Significance Different (LSD) test. The identification results showed that the Ferokop attractant had the highest attractiveness, at 337.38 catches per day, followed by the Petrogenol brand with 225.52 catches, and finally the Milabu brand with 83.05 catches. The conclusion is that the three types of attractant brands have different abilities in attracting male fruit flies.